Salicylanilide esters of N-protected amino acids as novel antimicrobial agents - Imramovský, Ales; Vinsová, Jarmila; Férriz, Juana Monreal; Buchta, Vladimír; Jampílek, Josef (Bioorganic & medicinal chemistry letters, 2009)
A series of novel, highly antimicrobial salicylanilide esters of N-protected amino acids were synthesized and characterized. Their in vitro antimicrobial activity against eight fungal strains and Mycobacterium tuberculosis was determined. The compounds had the highest level of activity against Aspergillus fumigatus, Absidia corymbifera and Trichophyton mentagrophytes, and these levels were higher than that of the standard drug fluconazole. In addition, three compounds showed interesting antituberculosis activity, with inhibition ranging from 89% to 99%. (S)-4-Chloro-2-(4-trifluoromethylphenylcarbamoyl)-phenyl 2-benzyloxy-carbonylamino-propionate had the highest level of both antifungal and antimycobacterial activity. The structure-activity relationships of the new compounds are discussed.
Keywords: aminokyseliny; Microbial Sensitivity Tests; Amino Acids; Absidia; salicylanilidy; Salicylanilides; mikrobiální testy citlivosti; Anti-Infective Agents; Aspergillus fumigatus; Esters; antiinfekční látky; Mycobacterium tuberculosis; Trichophyton; estery